Blood eosinophil level and lung function trajectories: cross-sectional and longitudinal studies in European cohorts. Issue 4 (5th October 2020) - Mogensen, Ida; Vonk, Judith M.; Wijnant, Sara R.A.; Zhou, Xingwu; Boezen, H. Marike; Brusselle, Guy; Lahousse, Lies; Janson, Christer; Malinovschi, Andrei
Background: Elevated blood eosinophils have been associated with lower lung function and are believed to be associated with accelerated lung function decline. Method: Blood eosinophils were measured in four cohorts: <45 years cohort within the Vlagtwedde–Vlaardingen (V&V) study, the Uppsala cohort of the European Community Respiratory Health Survey (ECRHS-Uppsala; <45 years), ≥45 years cohort within the V&V study, and the Rotterdam study (≥45 years). Blood eosinophils at baseline were classified as normal (<300 cells·μL −1 ) or elevated (≥300 cells·μL −1 ). Lung function was measured at baseline and follow-up with spirometry: forced expiratory volume in 1 s (FEV1 ), vital capacity (VC) and their ratio FEV1 /VC. The association between blood eosinophils and lung function was tested cross-sectionally using linear regression and longitudinally using a mixed model, both adjusted for age, sex, height, pack-years smoking and smoking status. Stratified analyses were done for asthma. Results: Elevated blood eosinophils were associated with lower FEV1 (regression coefficient −147 mL (95% CI −188 to −105 mL)), VC (−120 mL (−165 to −75 mL)) and FEV1 /VC (−1.3% (−1.9% to −0.6%)) at baseline in the two <45 years cohorts, and with lower FEV1 (−70 mL (−112 to −27 mL)) and FEV1 /VC (−1.8% (−2.6% to −1.0%)) in the two ≥45 years cohorts. Elevated blood eosinophils were associated with an accelerated decline in FEV1 (−5.5 mL·year −1 (95% CI −10.5 to −0.5 mL·year −1 )) and VC (−6.4 mL·year −1 (−11.26 to −1.5 mL·year −1 )) compared to normal blood eosinophils in the younger asthmatic subjects in the longitudinal studies. Conclusion: Elevated blood eosinophils are associated with lower lung function in the general population and with an accelerated lung function decline among asthmatic individuals. Elevated blood eosinophils (≥300 cells per μL) associate with lower lung function in an adult general population and with a worse lung function trajectory in adult asthmatic individuals https://bit.ly/3fJJ10h